ECONOMIA E PODER EMPRESARIAL NO BRASIL E NA AMÉRICA LATINA: novas perspectivas empíricas e metodológicas - Salles Pereira dos Santos, Rodrigo; Palazzo Dias, Rodolfo; Aguiar, Thiago (Caderno CRH, 2024)